Exploring the Economic Benefits of the Halal Certification in International Trade: A Literature Review - Muhammad Cholil; Mamduh, Muhammad Faizul; Pertiwi, Tanza Dona; Cipto, Disca Aprilinda; Herianingrum, Sri (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
This study explores the economic benefits of the halal industry and its role in driving international trade growth. The rapid expansion of the halal industry, driven by the growing global Muslim population, presents significant opportunities in the global supply chain. As the country with the largest Muslim population, Indonesia has the potential to strengthen its economy by enhancing halal product exports. Using a descriptive-qualitative approach through literature review, this study examines strategies for developing Indonesia’s halal industry based on local wisdom and industry potential. To compete globally, Indonesia must optimize key halal sectors such as food, beverages, pharmaceuticals, cosmetics, and emerging industries like fashion and the creative economy. This study offers a recommended model for a competitive global halal market, providing insights for government institutions, industry practitioners, and academics in supporting Indonesia’s vision to lead the global halal industry.